2009
DOI: 10.1017/s1461145709009924
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for pro-inflammatory cytokines in regulating synaptic plasticity in major depressive disorder

Abstract: A growing body of data suggests that hyperactivation of the immune system has been implicated in the pathophysiology of major depressive disorder (MDD). Several pro-inflammatory cytokines, such as tumour necrosis factor-alpha (TNF-α) and interleukin-1 (IL-1) have been found to be significantly increased in patients with MDD. This review focuses on these two cytokines based on multiple lines of evidence from genetic, animal behaviour, and clinical studies showing that altered levels of serum TNF-α and IL-1 are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
198
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(204 citation statements)
references
References 197 publications
(197 reference statements)
2
198
2
2
Order By: Relevance
“…We are, however, unable to examine the effect of in utero cigarette smoke exposure, which is a risk factor for both depression and asthma in the offspring (43,44). Depression is also associated with high systemic levels of inflammatory cytokines, particularly TNFa, which, in turn, has a pathogenic role in asthma (45,46). Finally, a potential neuroendocrine mechanism involves depression-related alteration in the hypothalamic-pituitary-adrenal axis that For definition of abbreviation, see Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…We are, however, unable to examine the effect of in utero cigarette smoke exposure, which is a risk factor for both depression and asthma in the offspring (43,44). Depression is also associated with high systemic levels of inflammatory cytokines, particularly TNFa, which, in turn, has a pathogenic role in asthma (45,46). Finally, a potential neuroendocrine mechanism involves depression-related alteration in the hypothalamic-pituitary-adrenal axis that For definition of abbreviation, see Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that gene variants that contribute to an augmented inflammatory response are associated with the pathogenesis of many diseases including psychiatric disorders [36,37]. Independent genetic polymorphism (Table 2) and gene expression (Table 3) In addition, there is now evidence that receptors for the pro-inflammatory cytokines, such as TNF-α, IL-1β, IL-6 and the IFNs, are constitutively expressed in the hippocampus, thalamus, hypothalamus, dentate gyrus and cortex [90]. and infectious diseases and in several brain pathologies [91].…”
Section: Introductionmentioning
confidence: 99%
“…The increased production of proinflammatory cytokines and infiltration of peripheral immune cells into the central nervous system (CNS) are closely associated with neuronal damage in the spinal cord and many brain regions (6)(7)(8)(9)(10). Elevation of several cytokines such as TNF-α and IFN-γ precedes infiltration of peripheral immune cells and could have a significant impact on neuronal function (11)(12)(13)(14)(15)(16)(17)(18)(19), potentially contributing to early sensory and cognitive impairments. However, the link between the cytokine elevation and CNS deficits in autoimmune diseases remains unclear.…”
mentioning
confidence: 99%